2020
DOI: 10.1186/s12877-020-1448-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the shoe really fit? Characterising ill-fitting footwear among community-dwelling older adults attending geriatric services: an observational cross-sectional study

Abstract: Background: Falls in older people are common and can result in loss of confidence, fear of falling, restriction in activity and loss of independence. Causes of falls are multi-factorial. There is a paucity of research assessing the footwear characteristics among older people who are at high risk of falls, internationally and in the Irish setting. The aim of this study was to examine the proportion of older adults attending a geriatric day hospital in Ireland who were wearing incorrectly sized shoes. Methods: A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…6 Even though no serious injury is caused, ill-fitting footwear causes loss of confidence, a fear of falling, and a restriction in activity. 30 Our findings are in line with those reported in the literature in that aspect At the beginning of the study, it was considered that wearing appropriate-fitting footwear reduces the fear of falling in older adults. Consistently, the number of repetitive falls in the last year was less in the group wearing suitable shoes than the other group in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6 Even though no serious injury is caused, ill-fitting footwear causes loss of confidence, a fear of falling, and a restriction in activity. 30 Our findings are in line with those reported in the literature in that aspect At the beginning of the study, it was considered that wearing appropriate-fitting footwear reduces the fear of falling in older adults. Consistently, the number of repetitive falls in the last year was less in the group wearing suitable shoes than the other group in our study.…”
Section: Discussionsupporting
confidence: 92%
“…27,29 One study comparing appropriate-fitting and ill-fitting shoes showed that wearing ill-fitting shoes did not have an effect on TUG scores. 30 In the present study, it was shown that functional performance did not change according to footwear suitability.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Use of inappropriate footwear was very common in this cohort and similar rates have been reported by other inpatient and outpatient studies of older adults [17,56,57]. Footwear interventions have been shown to improve foot pain and function [58,59].…”
Section: Discussionsupporting
confidence: 83%
“…Improperly selected footwear may intensify age-related foot changes, be a direct cause of pain, health disorders of the feet and higher parts of the kinematic chain, and reduce the comfort of locomotion and the ability to undertake everyday life activities (Jiménez-Ormeño et al, 2011;Ikpeze, Omar & Elfar, 2015;Hinojo-Pérez et al, 2016;Jellema et al, 2019). It may cause pressure on some parts of the foot, change the distribution of pressure forces on the foot, thereby increasing the anteroposterior and mediolateral tilts of the body's centre of gravity, which, combined with weakening posture control mechanisms, predisposes to loss of balance and, consequently, to falls (Hatton et al, 2013;Ikpeze, Omar & Elfar, 2015;O'Rourke et al, 2020). The use of excessively worn or slippery footwear has a negative effect, as well as its improper construction, e.g., wrong height of the heel or upper, heel stiffening (Saghazadeh, Kitano & Okura, 2015).…”
Section: Introductionmentioning
confidence: 99%